Mimicking the bioelectrocatalytic function of recombinant CotA laccase through electrostatically self-assembled bioconjugates. Issue 4 (10th January 2019) - Alba-Molina, David; Rodríguez-Padrón, Daily; Puente-Santiago, Alain R.; Giner-Casares, Juan J.; Martín-Romero, María T.; Camacho, Luis; Martins, Lígia O.; Muñoz-Batista, Mario J.; Cano, Manuel; Luque, Rafael
Abstract : Unprecedented 3D nanobiosystems provide excelling oxygen electroreduction performance. Abstract : Unprecedented 3D nanobiosystems composed of recombinant CotA laccases and citrate-stabilised gold nanoparticles have been successfully achieved by an electrostatic self-assembly strategy. The bioelectrochemical reduction of O2 driven by CotA laccase at the spore coat was mimicked. Consequently key insights into its bioelectrocatalytic function were unravelled.